Comparative Analysis of Different Graphite Concentrations in Micro-PMEDM Drilling - Chiara Ravasio; Giuseppe Pellegrini; Giuseppe Rosace; Valentina Trovato (Journal of Manufacturing and Materials Processing)
Micro-electrical discharge machining is valuable in industry thanks to its ability to realise precise micro-holes with high aspect ratios. However, a limitation of the technology is represented by its low material removal rate compared to other material removal technologies. Therefore, different strategies are under investigation to make the process faster. One of these strategies consists of adding powders into the dielectric. This process is called powder-mixed electrical discharge machining (PMEDM). This paper focusses on the optimisation of different aspects of this process, particularly the effects of the powder concentration, the presence of the surfactant, the stirring of the dielectric during the machining and the stability in time of the dielectric in micro-drilling. Graphite was used as powder in pure water, and in some tests a dispersant was also added. The concentration of the powder was varied, maintaining the same ratio between the graphite and the surfactant. The optimal graphite concentration was also used without the dispersant but with a changed parameter for the stirring system. The powder-mixed dielectrics showed better removal performance than pure water, and the best graphite concentration was the highest. The material removal rate increased by 40–150% compared to pure water. The tests made without dispersant showed that its presence did not improve the machining rate, while the stirring system deeply affected the process. The electrode wear benefitted from the reduction in machining time, and when the dispersant was used, electrode wear was lowered up to 50% compared to pure water. The trend of the electrode law of motion was affected by the concentration of the contaminant (debris from the erosion and powder). The geometrical characteristics were also affected by the presence of the powder, which changed the spark length. With the highest graphite concentration, radial overcut increased up to 50% compared to pure water. The stability in time of the dielectric when the powder was added was also evaluated and it was found that an efficient stirring system without the use of dispersant is a good solution, able to limit the possible sedimentation and aggregation of the powder.